Non-linear relationship between foreign currency derivatives and firm value: evidence on Shariah compliant firms - Zamzamir@Zamzamin, zaminor; Haron, Razali; Ahmad Bahurul Ulum, Zatul Karamah; Abdullah Othman, Anwar Hasan (Emerald, 2021)
This study examines the impact of hedging on firm value of Shariah compliant firms (SCFs) in a –non-linear framework. Design/methodology/approach This study employs the system-GMM for dynamic panel data to examine the influence of derivatives usage on firm value (Tobin’s Q, ROA and ROE). The sample comprised of 59 non-financial SCFs engaged in derivatives from 2000 to 2017 (18 years). The Sasabuchi-Lind-Mehlum (SLM) test for U-shaped is performed to confirm the existence of the non-linear relationship. Findings This study concludes that hedging significantly contributes to firm value of SCFs based on the non-linear framework. This study suggests that, first, the non-linear relationship occurs due to the different degree of derivatives usage and risk. Second, firms practice selective hedging to maintain the upside potential of firm value. Research limitations/implications This study has important implications. First, the importance of risk –management via derivatives to increase firm value, second, the evidence of selective hedging from the non linear relationship between derivatives and firm value and third, the need for quality reporting on derivatives engagement by firms in line with the required accounting standard on derivatives. Originality/value This study fills the gap in the literature in relation to the risk management strategies of –SCFs in three aspects. First, re-examines the relationship using recent data. Second, examines the relationship in the non-linear framework as the limited studies found in the literature on Malaysian firms are only based on linear relationship. Third, determines whether hedging undertaken by firms is optimal as this can only be addressed using the non-linear framework. This study is robust to the various definitions of firm value (Tobin’s Q, ROA and ROE) and non-linear methodologies.